Subarachnoid block for caesarean section in severe preeclampsia - Chaudhary, Sujata (Medknow Publications Pvt Ltd, 2011)
Pregnancy-induced hypertension constitutes a major cause of morbidity and mortality in developing nations and it complicates about 6–8% of pregnancies. Severe preeclampsia poses a dilemma for the anesthesiologist especially in emergency situations where caesarean deliveries are planned for uninvestigated or partially investigated parturients. This article is aimed to review the literature with regards to the type of anesthesia for such situations. A thorough search of literature was conducted on PubMed, EMBASE, and Google to retrieve the articles. Studies on parturients with severe preeclampsia, undergoing caesarean section, were included in this article. There is growing evidence to support the use of subarachnoid block in such situations when the platelet counts are >80,000 mm(-3). Better hemodynamic stability with the use of low-dose local anesthetic along with additives and better neonatal outcomes has been found with the use of subarachnoid block when compared to general anesthesia.